Aggravated blistering and increased deuterium retention in iron-damaged tungsten after exposure to deuterium plasma with various surface temperatures. (26th July 2018) - Zhu, Xiu-Li; Zhang, Ying; Kreter, Arkadi; Shi, Li-Qun; Yuan, Yue; Cheng, Long; Linsmeier, Christian; Lu, Guang-Hong
Abstract: Effects of iron ion pre-irradiation with energy of 1 MeV on deuterium retention and blistering in tungsten has been investigated after exposure to low-energy (40 eV) and high flux (~10 22 D m −2 s −1 ) deuterium plasma under high fluence of 1  ×  10 26 D m −2 with various surface temperatures (450 K, 550 K and 750 K). The undamaged and pre-damaged tungsten show a similar temperature dependence of deuterium-induced blistering, as well as deuterium retention in the near surface (within 300 nm). Deuterium concentration in the near surface decreases with increasing the surface temperature in deuterium plasma exposure. For both cases, the most serious blistering is present at the surface temperature of 550 K. Due to the creation of pre-damage the size of surface blister becomes much larger and the near-surface deuterium concentration becomes higher. Analysis of blistering-related cavities in the pre-damaged and undamaged tungsten indicates that in pre-damaged tungsten deuterium aggregates in the place with a much larger depth. Based on the comparison of the pre-damage induced increment of deuterium retention within the near surface region (damage layer) and in the bulk, it reveals that the pre-damage enhances deuterium retention in the bulk more strongly than that in the near-surface region, suggesting that the deuterium flux diffusing into the bulk of pre-damaged tungsten is largely improved.